2021
DOI: 10.1155/2021/1257283
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine Ameliorates Cardiac Function in Heart Failure with Preserved and Reduced Ejection Fraction via Upregulation of miR‐133a

Abstract: Heart failure (HF) is a clinical syndrome caused by impairment of ventricular filling, ejection of blood, or both and is categorized as HF with reduced ejection fraction (HFrEF) or HF with preserved ejection fraction (HFpEF) based on left ventricular function. Cardiac fibrosis contributes to left ventricular dysfunction and leads to the development of HF. Ivabradine, an If current selective specific inhibitor, has been shown to improve the prognosis of patients with HF. However, the effects of ivabradine on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Furthermore, several studies have found that ivabradine can improve cardiac function through alternative mechanisms: ivabradine reduces adverse remodeling and injury in the heart by inhibiting calcium overload induced by increased I f current ( 31 ). Shuai et al ( 32 ) found that ivabradine ameliorated pressure overload-induced myocardial fibrosis and cardiac dysfunction by upregulating miR-133a in mice. Ivabradine may mediate the immunomodulatory and anti-inflammatory effects independent of heart rate reduction ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have found that ivabradine can improve cardiac function through alternative mechanisms: ivabradine reduces adverse remodeling and injury in the heart by inhibiting calcium overload induced by increased I f current ( 31 ). Shuai et al ( 32 ) found that ivabradine ameliorated pressure overload-induced myocardial fibrosis and cardiac dysfunction by upregulating miR-133a in mice. Ivabradine may mediate the immunomodulatory and anti-inflammatory effects independent of heart rate reduction ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the target for miR-133a-3p was Igf1r, a component of the IGF1R/PI3K/AKT signaling pathway, which is important for cell survival (73). In contrast, cardiac miR-133a was reduced in TAC mouse model and an in vitro fibrosis model using neonatal rat primary ventricular fibroblasts treated with Ang-II (137), again indicating that miRNAs can be differently regulated in diastolic vs. systolic HF.…”
Section: Mir-133amentioning
confidence: 99%
“…Ivabradine, a funny current ( I f ) inhibitor, reduces heart rate without reducing cardiac inotropy [ 129 ] and may have some positive effects on cardiac fibrosis via upregulation of microRNA-133a, which targets connective tissue growth factor and collagen 1 in cardiac fibroblasts [ 130 ]. To date, two randomized controlled trials [ 131 , 132 ] and one cross-over study [ 133 ] have been conducted to evaluate the usefulness of ivabradine in patients with HFpEF.…”
Section: Emerging Drug Therapies For Hfpefmentioning
confidence: 99%